Design of lightweight bicycle travel frames for road cycling - Li, Xiaoyang (2016)
Bicycles have an increasing demand and importance in urban transportation and travel. However, the large size of the bicycle also increases the difficulty of shipping in long-distance travel. The purpose of this report is to present the coupling designs for stainless steel demountable bicycle frame which allows users to separate and pack the bicycle frame into a suitcase to facilitate the travel for cyclists. The existing demountable bicycle frames were reviewed for better understanding of the mechanism of coupling design. To determine the location of couplings, the 3D model of bicycle frame simulated three standard loading conditions to understand the stress distribution over bicycle frame. For coupling design, the design methods such as function analysis, decision matrix and embodiment design are utilized to generate three coupling design concepts. Finite Element Analysis was conducted to test the stability and safety of each design, which also provided the guide for further modification. Prototypes of four final designs were completed by 3D printing for better product presentation. Possible further implementations were also proposed in the report.